SENTANA RAJEG DAN NILAI ANAK LAKI-LAKI BAGI KOMUNITAS BALI DIASPORA DI KABUPATEN KONAWE - Yohanes Krismantyo Susanta (Harmoni, 2019)
The issue of gender inequality experienced by women is not something new. Women have long been treated unfairly and discriminatively in relation to their roles and positions. Similarly, in terms of duties and responsibilities as a wife who is required to bear children. This study aims to find out how the condition of Balinese women who are in overseas in the face of demands for childbearing sons. The method used is qualitative research with in-depth interviews (indepth interview) using the research question guide. The results show that women in the overseas (Konawe District) still face discrimination and are required to have offspring (sons). In the context of the Balinese society which prioritizes male domination, the failure to have offspring is seen as the fault of the women. Therefore, the participation of religious and community leaders in eroding the gender injustice practices is needed.